Relation between over-democratisation and luxury fashion brand image - Christiane Beyerhaus; Lisa Gockeln (ISM Research Journal, 2017)
In this day and age, luxury companies embrace the changing face of luxury by opening up their brands to a broader and more contemporary customer group. It includes expanding portfolios with entry-level products, extending the distribution channels and offering lines built upon more affordable pricing strategies. Clearly, this trend raises questions concerning the notion of luxury and the influence on luxurious brand associations, especially in times when brands overstrain their democratisation endeavors by becoming too accessible. Therefore, the purpose of the present study is to investigate the effect of over-democratisation on a luxury brand image. In order to achieve this, luxury expert's perceptions towards over-democratisation and related real-life brand examples were gathered by means of structured interviews. These served as a basis for a subsequent quantitative study, which facilitated to identify and compare the images of given over-democratised brands as against those of well-democratised brands. In accordance with the findings of this research it can be concluded that over-democratisation indeed has a negative effect on the image of a luxury brand. The model, which was derived from the analysis, particularly demonstrates that symbolic image associations have suffered from a luxury brand's overstretching, while functional associations were only slightly weakened or even endorsed. Therefore, brands that intend to preserve their luxurious positioning, while opening up to a wider audience, are alerted to especially protect symbolic brand cues by building upon emotional and psychological bonds to create long-term desires and sustainably fuel the luxury dream.
Keywords: 650